Garden Packet Yields Mixed Results - Mark Claesgens (Journal of Applied Communications, 1985)
The 1984 second annual home gardening packet prepared by the WSU College of Agriculture and Home Economics Information Department saw an increase in readership but a decline in the number of participating papers from 1983.